BETWEEN AWARENESS AND ACTION: UNDERSTANDING PUBLIC PARTICIPATION IN WASTE SORTING AND WASTE BANK PROGRAMS - Andante Hadi Pandyaswargo; Indriyani Rachman; Meilinda Fitriani Nur Maghfiroh; Vicka Kharisma; Hiroshi Onoda (Universitas Trisakti, 2025)
Aim: Waste sorting at-source is vital for sustainable waste management and the circular economy in Indonesia. Despite regulations, community programs, and digital interventions, sorting remains limited. This study explores self-reported sorting behaviors among urban residents and examines how waste banks may enhance participation. Methodology and results: We surveyed 220 respondents from Indonesian major cities and applied Two-Step Cluster Analysis and chi-square tests to assess links between sorting behavior, socio-demographics, and waste bank participation. The main barriers were lack of space and time. The 57 respondents with access to a waste bank, only 14 were members; 43 were uninterested, often citing inconvenience. Active members were positive about the possibility of automation technologies, including automated sorting and collection, weighing machines for pricing, and digital payments. Many also suggested a mobile app to track deposits. Conclusions, Significance, and Impact: Technological innovations paired with incentives potentially reduce participation barriers. Integrating digital and automated solutions with behavioral insights may help overcome current limitations and foster a more effective circular economy in Indonesia.